Exploring patient perspective: using narrative DIPEx interviews and the ICF model for interprofessional learning - Glässel, Andrea; Hippold, Ilona (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe International Classification of Functioning, Disability, and Health (ICF) has been widely adopted in academic health profession education and is part of bachelor curricula since its introduction by the WHO in 2001. In this context, interprofessional exchange among health professionals from a biopsychosocial perspective has become increasingly important and is now a key part of bachelor's program curricula to learn with, about, and from each other regarding students’ curiosity about interprofessional collaboration (IPC). This pilot study describes initial teaching experiences within an interprofessional elective module for health professions focused on patient-centeredness. It uses the ICF model to exemplify interprofessional exchange based on real patient experiences from the “DIPEx” database, which stands for “Database of Individual Patients’ Experiences.”MethodsBachelor students from four healthcare professions learned in small interprofessional groups and selected case-related content from excerpts of real patient narratives from qualitative interviews in the DIPEx database. In a peer-to-peer process, students structured, analyzed, and reflected on selected patient experiences and presented their findings using the ICF model.OutcomeDevelop a shared understanding of the case from a biopsychosocial perspective using the ICF model to communicate and reflect on patient-centeredness in interprofessional groups for a common care strategy rooted in patient-centeredness.ConclusionThis study illustrates how the shared analysis of a patient's experience of illness can lead to different perspectives on professional concepts for practice. The ICF model serves as a guiding structure and analysis tool. The core of the IPC, patient-centeredness, becomes the focus of the collaborative actions of the health professions.